Analisis Bibliometrik Menggunakan VOSviewer Terhadap Publikasi Artikel Jurnal Gema Pustakawan di Google Scholar - Hasnidar; Thamrin Hasan; Hadriani (Jurnal Gema Pustakawan, 2023)
Bibliometrics is a bibliographic analysis method used to study the structure, development and dynamics of scientific publications. This research focuses on bibliometric analysis of articles contained in the Gema Librarian Journal which were published in 2013-2023. This research aims to find out what topics are contained in the Gema Librarian Journal, and which articles are most frequently cited. This research data was collected by searching Gema Librarian Journal articles via Google Scholar, then continuing by creating a list of articles sorted by year of publication by including the name of the researcher and the title of the article with the help of Microsoft Excel. The results of this research show that the study topics found based on visualization network analysis from VOSViewer show that there are 100 study topic items in the Gema Librarian journal. A total of 100 items on this topic were grouped into 15 clusters by the VOSViewer application with 229 links and a total link strength of 254. Furthermore, the most frequently cited article was a research article with the title "Study of the Use of Online Journals at the Riau University Pekanbaru Library". This research was conducted by Thamrin Hasan. The number of citations for this article was 27 citations or 55.36%. The conclusion of this study is that bibliometric research on the Gema Librarian Journal shows a diversity of study topics with 15 clusters, while the article "Study of the Use of Online Journals at the Riau University Pekanbaru Library" is the most frequently cited article.